Emerging international compliance: Policy implications of a money laundering case - Isolauri Emilia; Zettinig Peter; Nummela Niina (Palgrave Macmillan, 2022)
By conducting a qualitative single case study, we have depicted in this study a suspected case of international money laundering in Finland, and described its consequences in terms of policy changes. The case allowed us to investigate how new anti-money laundering policies emerge over time and thus advance knowledge relevant to formulating effective international business policies. Building on institutional heterogeneity and the co-evolutionary nature of change, we have proposed a new framework depicting emerging international compliance in order to promote understanding of this complex, yet dynamic phenomenon. The literature repeatedly highlights the role of formal policies in mitigating international money laundering, however, we have paid additional attention to unethical business practices and the moral aspect recognised to be important in terms of curbing the problem. This is particularly relevant for MNCs, as they can aid institutional change internationally by spreading ‘company best practices’. We also present the managerial and policy implications of solving moral problems related to money laundering from the perspective of governments, society and organisations.